(untitled) - Triệu, Thị Chơi (Singapore, 2005)
The cuisine of Vietnam is widely regarded as one of the finest in the world. This collection of recipes, gathered from the top kitchens of this vast country, presents an exciting range of dishes. With emphasis on fresh ingredients and light seasonings, Authentic Recipes from Vietnam is ideal for the health-conscious cook. Recipes in this book were provided by Trieu Thi Choi and prepared by the chefs of the Saigon Floating Hotel, in Ho Chi Minh City, and coordinated by Marcel Isaak.
Keywords: Cookery; Vietnamese,Việt Nam; Nấu ăn